Differences in kinetics, kinematics and muscle activation strategies in male and female team sport athletes during unanticipated sidestepping - Weir, G.; Stillman, M.; van Emmerik, R.; Wyatt, H.; Jewell, C.; Hamill, J. (Journal of Science in Sport and Exercise, 2019)
Purpose: The purpose of this study was to compare kinetics, kinematics and muscle activation strategies between male and female collegiate level athletes during unanticipated sidestepping tasks to further the understanding of sex-specific differences in injury incidence and their potential influence on ACL injury risk. Methods: Three-dimensional kinematics, ground reaction forces and surface electromyography of eight lower limb muscles were recorded during unanticipated sidestepping in 20 male soccer and 17 female field hockey National Collegiate Athletics Association Division 1 athletes. Trunk, hip and knee kinematics, knee joint moments, total muscle activation (TMA: knee, gluteal, quadriceps, hamstrings and gastrocnemii) and directed co-contraction ratios (DCCR) were compared between groups with two-sample t tests. Results: No sex differences were observed for peak frontal and transverse plane knee moments (P > 0.05), however males had 10% greater knee flexion moments (P = 0.047). Females had lower hip flexion and abduction and greater hip internal rotation angles than males likely concomitant with the 30% reduction in gluteal TMA (P < 0.05). Females had lower quadriceps TMA during pre-contact and weight acceptance and higher hamstrings TMA during weight acceptance (P < 0.05). Group averages for DCCR were not representative of individual patterns, where the majority of males were quadriceps dominant compared with females. Conclusions: Female and male team sport athletes display similar frontal and transverse plane knee moments, however their ability to support/counter the load applied (i.e., muscle activations strategies) to the knee joint differed.